Painless ovarian tumor mimics ovarian cancer with all ligaments spontaneously detached: A case report - Hsiang-Chun Dong; Mu-Hsien Yu; Her-Young Su (Elsevier, 2018)
Objective: Ovarian tumor is a frequently encountered gynecological disease. The tumor is usually anchored by a pedicle. In rare cases, it may detach and derive nourishment from other abdominal structures to which it adheres. Even rarer is for the tumor to be freely mobile, with no ligamentous attachment. Case report: A 21-year-old woman with delayed menstruation and chronic low abdominal pain for months, had a well-defined cystic lesion of approximately 9 × 9 cm in the middle of the pelvis, identified on transabdominal sonography and abdominal computed tomography. During an exploratory laparotomy, we found an ovarian tumor on the left side of the pelvis, in which the pedicle had spontaneously detached; it was removed without dissection or resection. The tumor was well-encapsulated and suspended without any ligament attachments. Conclusion: Freely mobile ovarian tumors with all ligaments spontaneously detached may be misdiagnosed because there is no pain caused by torsion. The absence of blood flow leads to internal necrosis, easily mistaken for malignancy or other diseases. Also, the location may change from the time images are captured until surgery. Surgery is the best option, regardless of the final diagnosis. Keywords: Exploratory laparotomy, Ovarian tumor, Torsion, Spontaneously detached